Distinções polifônicas na dramaturgia contemporânea : em cena a escrita colaborativa do grupo XIX de teatro - Conceição, Jorge Wilson da (2016)
This doctoral thesis describes and analyses four collaborative creative processes of dramaturgy by Grupo XIX de Teatro from Sao Paulo, namely: Hysteria, Hygiene, Marcha para Zenturo e Nada aconteceu, tudo acontece, tudo está acontecendo. The basis of this study are the concepts of collaborative process and polyphony, as a set of voices which resounds from a play. The goal was to investigate the hypothesis that there are three different polyphonic modus which characterizes the productions of the group. In order to confirm that, the study analyzed the contribution of the artists, the public, as well the researches of the group. Besides, it has mapped the writing strategies used by the group to create the play Nada aconteceu, tudo acontece, tudo está acontecendo (Nothing has happened, everything happens, everything is happening) in relation to Vestido de noiva (Wedding dress), by Nelson Rodrigues. In this case, the objective was to understand the relevance of the dialogue of the work by Nelson Rodrigues as a basis for the contemporary dramaturgy by Grupo XIX de Teatro. The final hypothesis concerns the ineffectiveness of labels like adaptation of or freely inspired by in the tentative of naming creative processes of complex nature. The research has interviewed two actors of the group and gathered other contributions from other artists of the group. Besides, the research has analized the texts of the plays, documents, videos, reviews and other writings upon them, as well as some records from our own observation as audience. The results have confirmed our hypothesis about the different polyphonic processes, stating that the ones which are totally based on collaboration present more evidence of polyphony. Regarding the process of retelling Vestido de noiva, it was found evidences of a totally original work created by the group. To complete, the study suggests that contemporary dramaturgy produced by many theater groups should be seen as a rhizomatic one, due to its complexity and the dialogue with a variety of literature genders and Art languages, as well as different authors